The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/1469-0691.12295
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as a source of anti-Toxoplasma gondii IgG for enzyme immunoassay in human samples

Abstract: Toxoplasmosis, a highly prevalent disease, is mainly diagnosed by serology. Incidence studies could be feasible in children, but ethical concerns restrict blood sampling in this group. Saliva contains small amounts of crevicular fluid IgG. Dot-ELISA and a protein A IgG capture immunoassay were standardized for anti-Toxoplasma gondii IgG in paired saliva and serum samples from 20 adult volunteers. A frequency of toxoplasmosis of 19% (95% CI 12-28) was found in 100 saliva samples from university graduates using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 12 publications
0
19
2
4
Order By: Relevance
“…Previous reports have shown that anti‐ T. gondii IgG, IgM and IgA abs are present in saliva. In some studies, the salivary IgA and IgG levels reflect those in serum, but they show low sensitivity and specificity values, as in the present study . To our knowledge, searches of anti‐ T. gondii IgG subclasses have not been performed in saliva.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Previous reports have shown that anti‐ T. gondii IgG, IgM and IgA abs are present in saliva. In some studies, the salivary IgA and IgG levels reflect those in serum, but they show low sensitivity and specificity values, as in the present study . To our knowledge, searches of anti‐ T. gondii IgG subclasses have not been performed in saliva.…”
Section: Discussioncontrasting
confidence: 58%
“…In some studies, the salivary IgA and IgG levels reflect those in serum, but they show low sensitivity and specificity values, as in the present study. [10][11][12][13][14][15][16] To our knowledge, searches of anti-T. gondii IgG subclasses have not been performed in saliva. We hoped they could help diagnose or suggest prognosis, but we found a rather different panorama, as they performed badly, mainly because most positive cases for specific IgG2, IgG3 and IgG4 abs in saliva were negative in serum and did not correlate to IgG abs either; thus, they exhibited very low diagnostic parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These attributes could help fill gaps in infectious disease surveillance in populations typically underrepresented in health research including those in remote and resource-limited settings and children and pregnant women. Tests using oral fluid have been developed for human immunodeficiency virus (HIV) [10, 11], hepatitis A virus [12], hepatitis C virus [1214], norovirus [15, 16], Cryptosporidium parvum [1517], cytomegalovirus [18], Helicobacter pylori [15], and Toxoplasma gondii [19, 20] and been shown to yield similar sensitivities and specificities as serum-based ELISAs to assess past and recent infection.…”
Section: Introductionmentioning
confidence: 99%
“…IgA antibodies together with IgM and IgG against antigens derived from tachyzoite forms of T. gondii are frequently detected in sera of patients in the early and chronic phase of toxoplasmosis [20]. The presence of IgG and IgA anti-T. gondii in saliva and other body fluids has also been reported [21][22][23][24][25]. However, the specific role of IgA against T. gondii in the human oral cavity remains elusive.…”
Section: Introductionmentioning
confidence: 99%